The influence of shopping environment on impulsive buying : a study of online and in-store context, with the exploration of self-regulation - Baudracco, Célia (2024)
In an era where digital consumerism is quickly overtaking traditional retail models, this thesis studies the impact of shopping context - in-store versus online - on consumer impulsive buying behavior and explores the moderating role of self-regulation within these environments. Based on an in-depth literature review and using a quantitative approach with a consumer survey, this research evaluates impulsive purchase patterns across several shopping modalities. In comparison to in-store buyers, online shoppers exhibit much more impulsivity, according to statistical analyses such as t-tests and ANCOVAs. These results support the hypothesis that online environments with their ease of access, anonymity, and personalized marketing, facilitate higher impulsivity. Surprisingly, self-regulation does not significantly moderate the association between the shopping context and impulsive purchasing, indicating that the compelling aspects of online environments might surpass conventional self-control strategies. Moreover, the results point to the complex interaction between unique behavioral traits and environmental cues in retail settings, supporting the hypothesis that higher levels of self-regulation would be associated with more consistent in-store purchasing patterns. The thesis emphasizes how important it is for retailers to take these factors into account when creating plans to mitigate impulsive purchases, especially on online platforms, and the need for consumer education initiatives that improve knowledge related to self-control in retail settings. Future research should investigate the precise processes by which the instantaneity and ease of online shopping settings affect self-regulation. In the end, this thesis creates the framework for smarter retail strategies considering the particular characteristics of both shopping contexts.